Polyarteritis Nodosa with Tubercular Pericardial Effusion: A Rare Coexistence of Childhood Vasculitis and Infectious Disease - Ferdosh, Taslima; Islam, Mohammed Mahbubul; Talukder, Manik Kumar; Islam, Mohammad Imnul (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Polyarteritis nodosa (PAN) is a systemic vasculitis that affects medium-sized arteries, resulting in inflammation and damage to multiple organs. PAN may develop following bacterial or viral infections representing a post-infectious autoimmune response. Tuberculosis (TB) can affect any organ of the body and it is one of the most important causes of pericardial effusion in developing countries. This case report presents a young girl with a rare co-occurrence of PAN and tubercular pericardial effusion having a history of fever, polyarthritis, weight loss, digital gangrene, and respiratory distress. On examination, the patient had signs of heart failure, pericardial effusion, and diminished peripheral pulsation in both anterior and posterior tibial arteries and arteria dorsalis pedis. The patient improved dramatically after receiving combined immunosuppressive and anti-tubercular therapy. This case was a unique coexisting situation where the patient presented with unusual presentations and also demonstrated the complex interplay between autoimmune and infectious diseases which needs a comprehensive diagnostic and treatment approach. J Bangladesh Coll Phys Surg 2025; 43: 85-88